Assessment of Electrospun and Ultra-lightweight Polypropylene Meshes in the Sheep Model for Vaginal Surgery - Hympánová, Lucie; Rynkevic, Rita; Román, Sabiniano; Mori da Cunha, Marina G M C; Mazza, Edoardo; Zündel, Manuel; Urbánková, Iva; Gallego, Monica R; Vange, Jakob; Callewaert, Geertje; Chapple, Christopher; MacNeil, Sheila; et al. (European urology focus, 2020)
BACKGROUND: There is an urgent need to develop better materials to provide anatomical support to the pelvic floor without compromising its function. OBJECTIVE: Our aim was to assess outcomes after simulated vaginal prolapse repair in a sheep model using three different materials: (1) ultra-lightweight polypropylene (PP) non-degradable textile (Restorelle) mesh, (2) electrospun biodegradable ureidopyrimidinone-polycarbonate (UPy-PC), and (3) electrospun non-degradable polyurethane (PU) mesh in comparison with simulated native tissue repair (NTR). These implants may reduce implant-related complications and avoid vaginal function loss. DESIGN, SETTING, AND PARTICIPANTS: A controlled trial was performed involving 48 ewes that underwent NTR or mesh repair with PP, UPy-PC, or PU meshes (n=12/group). Explants were examined 60 and 180 d (six per group) post-implantation. INTERVENTION: Posterior rectovaginal dissection, NTR, or mesh repair. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Implant-related complications, vaginal contractility, compliance, and host response were assessed. Power calculation and analysis of variance testing were used to enable comparison between the four groups. RESULTS: There were no visible implant-related complications. None of the implants compromised vaginal wall contractility, and passive biomechanical properties were similar to those after NTR. Shrinkage over the surgery area was around 35% for NTR and all mesh-augmented repairs. All materials were integrated well with similar connective tissue composition, vascularization, and innervation. The inflammatory response was mild with electrospun implants, inducing both more macrophages yet with relatively more type 2 macrophages present at an early stage than the PP mesh. CONCLUSIONS: Three very different materials were all well tolerated in the sheep vagina. Biomechanical findings were similar for all mesh-augmented repair and NTR. Constructs induced slightly different mid-term inflammatory profiles. PATIENT SUMMARY: Product innovation is needed to reduce implant-related complications. We tested two novel implants, electrospun and an ultra-lightweight polypropylene textile mesh, in a physiologically relevant model for vaginal surgery. All gave encouraging outcomes.
Keywords: gynekologické chirurgické výkony; Animals; chirurgické síťky; Biocompatibility; Female; Vaginal surgery; Biomechanics; Prosthesis Design; biokompatibilní materiály; výsledek terapie; textilie; protézy - design; ženské pohlaví; ovce; pyrimidinony; prolaps dělohy; Treatment Outcome; Models, Animal; Biomaterials; Pelvic organ prolapse; Biocompatible Materials; Materials Testing; Uterine Prolapse; modely nemocí na zvířatech; Polypropylenes; Sheep; Disease Models, Animal; testování materiálů; Gynecologic Surgical Procedures; Pyrimidinones; polypropyleny; zvířata; Textiles; Surgical Mesh; modely u zvířat